Association of Cerebrospinal Fluid Neurofilament Light Protein Levels With Cognition in Patients With Dementia, Motor Neuron Disease, and Movement Disorders - Olsson, Bob (JAMA Neurol, 2018)
IMPORTANCE: Neuronal and axonal destruction are hallmarks of neurodegenerative diseases, but it is difficult to estimate the extent and progress of the damage in the disease process. OBJECTIVE: To investigate cerebrospinal fluid (CSF) levels of neurofilament light (NFL) protein, a marker of neuroaxonal degeneration, in control participants and patients with dementia, motor neuron disease, and parkinsonian disorders (determined by clinical criteria and autopsy), and determine its association with longitudinal cognitive decline. DESIGN, SETTING, AND PARTICIPANTS: In this case-control study, we investigated NFL levels in CSF obtained from controls and patients with several neurodegenerative diseases. Collection of samples occurred between 1996 and 2014, patients were followed up longitudinally for cognitive testing, and a portion were autopsied in a single center (University of Pennsylvania). Data were analyzed throughout 2016. EXPOSURES: Concentrations of NFL in CSF. MAIN OUTCOMES AND MEASURES: Levels of CSF NFL and correlations with cognition scores. RESULTS: A total of 913 participants (mean [SD] age, 68.7 [10.0] years; 456 [49.9%] women) were included: 75 control participants plus 114 patients with mild cognitive impairment (MCI), 397 with Alzheimer disease, 96 with frontotemporal dementia, 68 with amyotrophic lateral sclerosis, 41 with Parkinson disease (PD), 19 with PD with MCI, 29 with PD dementia, 33 with dementia with Lewy bodies, 21 with corticobasal syndrome, and 20 with progressive supranuclear palsy. Cognitive testing follow-up occurred for 1 to 18 years (mean [SD], 0.98 [2.25] years); autopsy-verified diagnoses were available for 120 of 845 participants with diseases (14.2%). There was a stepwise increase in CSF NFL levels between control participants (median [range] score, 536 [398-777] pg/mL), participants with MCI (831 [526-1075] pg/mL), and those with Alzheimer disease (951 [758-1261] pg/mL), indicating that NFL levels increase with increasing cognitive impairment. Levels of NFL correlated inversely with baseline Mini-Mental State Examination scores (ρ, −0.19; P < .001) in the full cohort (n = 822) and annual score decline in the full cohort (ρ, 0.36, P < .001), participants with AD (ρ, 0.25; P < .001), and participants with FTD (ρ, 0.46; P = .003). Concentrations of NFL were highest in participants with amyotrophic lateral sclerosis (median [range], 4185 [2207-7453] pg/mL) and frontotemporal dementia (2094 [230-7744] pg/mL). In individuals with parkinsonian disorders, NFL concentrations were highest in those with progressive supranuclear palsy (median [range], 1578 [1287-3104] pg/mL) and corticobasal degeneration (1281 [828-2713] pg/mL). The NFL concentrations in CSF correlated with TDP-43 load in 13 of 17 brain regions in the full cohort. Adding NFL to β-amyloid 42, total tau, and phosphorylated tau increased accuracy of discrimination of diseases. CONCLUSIONS AND RELEVANCE: Levels of CSF NFL are associated with cognitive impairments in patients with Alzheimer disease and frontotemporal dementia. In other neurodegenerative disorders, NFL levels appear to reflect the intensity of the neurodegenerative processes.